Unusual foreign body in rectum: a surgical curiosity - M., Soujanya; Kulkarni, Srinivas B.; S. R., Kruthi; M. P., Santosh; Prakash, O. G. (International Surgery Journal, 2021)
Rectal foreign bodies represent a unique and challenging field of surgical management which includes a careful history, physical examination and a high index of suspicion for complications. Foreign bodies are rarely seen in lower GI or rectum, inserted either accidently or for sexual satisfaction or to inflict harm. We have 3 case scenarios of unusual foreign body in rectum with varied clinical presentation, findings and three different methods of management/extraction done in our Institution. Patients present with common complaints of rectal or abdominal pain, constipation or obstipation, bright red blood per rectum, or incontinence. Initial step is to assess for peritonitis which is suggestive a perforation with intraperitoneal contamination and requires emergency exploratory. Erect Xray abdomen can reveal the presence of free air and the location of the object relative to the pelvic floor. A careful digital rectal examination is the most informative component of the evaluation process. Impacted foreign bodies may result in complications like intestinal obstruction, perforation of gut and peritonitis. Rectal foreign body is a diagnostic and management dilemma due to the delayed presentation owing to associated social stigma. Patients require a detailed examination and radiographic evaluation with resuscitation. Surgical intervention should be planned based on hemodynamic stability and presence/absence of perforation. Patient has to be referred to the psychiatrist for his perversion disorder, which is also mandatory for preventing recurrences.